Generation of a hiPSC line ZZUNEUi007-A from a patient with hypertrophic cardiomyopathy caused by mutation in MYH7 - Xiaowei Li; Yangyang Liu; Feifei Liu; Xiaojuan Wang; Mengduan Liu; Wenting Du; Jing Zhao; Mengyu Wang; Liang Hu; Chuchu Wang; Wanrong Fu; Jianzeng Dong; et al. (Stem Cell Research, 2020)
Hypertrophic cardiomyopathy (HCM) is the most common monogenic cardiovascular disorder. In this study, we generated human induced pluripotent stem cells (iPSC) ZZUNEUi007-A from dermal fibroblasts of an HCM patient with the p. R663H (c. 1988 G > A) mutation in MYH7. The generated hiPSC line had normal karyotype, showed robust expression of pluripotency markers and could differentiate into all three germ layers in vivo.